The Influence of Service Quality, and Price Toward Customer Satisfaction at PT. Juragan Wifi Indonesia - Rian, Muhammad Rian Ardianto; Basrah Saidani; Ika Febrilia (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2021)
The objectives of this study are: First, To determine the influence of Service Quality on Customer Satisfaction of PT Juragan Wifi Indonesia. Second, To determine the influence of Price on customer satisfaction of PT Juragan Wifi Indonesia. This research is conducted on 100 customers of PT. Juragan Wifi Indonesia that spread across Jakarta, Bogor, Depok, Tangerang, and Bekasi. Data is collected using a questionnaire with 5 point of likert scale, namely by reaching consumers by distributing the questionnaires which are then processed using the SPSS program. The results shows that service quality, and price provided by PT Juragan Wifi are valid and able to meet consumer expectations. Consumers of PT Juragan Wifi also have high level of satisfaction. Based on the results of hypothesis testing, it can be concluded that service quality has a positive effect on customer satisfaction, and price has a positive effect on customer satisfaction.